Restoration of Osteogenesis by CRISPR/Cas9 Genome Editing of the Mutated COL1A1 Gene in Osteogenesis Imperfecta - Jung, Hyerin (J Clin Med, 2021)
Osteogenesis imperfecta (OI) is a genetic disease characterized by bone fragility and repeated fractures. The bone fragility associated with OI is caused by a defect in collagen formation due to mutation of COL1A1 or COL1A2. Current strategies for treating OI are not curative. In this study, we generated induced pluripotent stem cells (iPSCs) from OI patient-derived blood cells harboring a mutation in the COL1A1 gene. Osteoblast (OB) differentiated from OI-iPSCs showed abnormally decreased levels of type I collagen and osteogenic differentiation ability. Gene correction of the COL1A1 gene using CRISPR/Cas9 recovered the decreased type I collagen expression in OBs differentiated from OI-iPSCs. The osteogenic potential of OI-iPSCs was also recovered by the gene correction. This study suggests a new possibility of treatment and in vitro disease modeling using patient-derived iPSCs and gene editing with CRISPR/Cas9.